The Influence of Fiberglass Fiber Arrangement Variations on the Tensile and Bending Strength of Ships - Muharom, Restu; Alamsyah; Hidayat, Taufik; Syahab , Husein (Indonesian Journal of Maritime Technology, 2024)
The use of Fiberglass Reinforced Plastic (FRP) as a substitute for wood in the shipbuilding industry in Indonesia is increasing, particularly in small vessels under 5 GT. Challenges in obtaining high-quality wood have driven fishermen and the shipbuilding industry to shift towards composite chopped materials such as fiberglass. This research aims to evaluate the tensile and bending strengths of fiberglass composites made using the hand lay-up method with variations of random fiber layers as well as fibers oriented at 0° and 90°. The tests were conducted according to ASTM D638-14 and D790 standards, with the results showing that the chopped-woven-hybrid fiber configuration produced the highest tensile strength of 38.174 MPa, while the chopped-chopped-woven-woven configuration produced the highest bending strength of 104.44 MPa. However, all the tested fiber layer variations did not meet the standards of the Indonesian Classification Bureau (BKI), indicating the need for further optimization in layer arrangement to achieve the desired quality. Additionally, the FRP boat-building training program conducted in Gisik Cemandi Village demonstrated that traditional boat craftsmen can adapt to this new technology, which offers an effective solution to wood scarcity while enhancing the quality and safety of vessels. This research supports the development of FRP as a more reliable, efficient, and environmentally friendly material for shipbuilding, particularly in the fisheries and small shipping sectors in Indonesia. The broader adoption of FRP technology is expected to address environmental and economic challenges in the national shipbuilding industry